2009
DOI: 10.1007/s10021-009-9232-x
|View full text |Cite
|
Sign up to set email alerts
|

Fog Water and Ecosystem Function: Heterogeneity in a California Redwood Forest

Abstract: Fog is thought to influence ecological function in coastal forests worldwide, yet few data are available that illuminate the mechanisms underlying this influence. In a California redwood forest we measured water and nitrogen (N) fluxes from horizontally moving fog and vertically delivered rain as well as redwood tree function. The spatial heterogeneity of water and N fluxes, water availability, tree water use, and canopy N processing varied greatly across seasons. Water and N fluxes to soil (annual average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
120
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 35 publications
6
120
0
1
Order By: Relevance
“…Synoptic conditions in these areas are conducive to the development of low-level stratocumulus clouds, which form just below the inversion base, typically several hundred meters above the sea surface (2,3). The advection of marine stratus over land profoundly moderates the coastal terrestrial climate by reducing insolation and temperatures, raising humidity, and supplying water directly to the landscape (4)(5)(6)(7)(8)(9)(10)(11)(12). The last effect is particularly notable along the active tectonic margin defining the Pacific coast of the Americas, where uplifted relief intercepts marine air and cloud moisture and blocks its inland penetration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synoptic conditions in these areas are conducive to the development of low-level stratocumulus clouds, which form just below the inversion base, typically several hundred meters above the sea surface (2,3). The advection of marine stratus over land profoundly moderates the coastal terrestrial climate by reducing insolation and temperatures, raising humidity, and supplying water directly to the landscape (4)(5)(6)(7)(8)(9)(10)(11)(12). The last effect is particularly notable along the active tectonic margin defining the Pacific coast of the Americas, where uplifted relief intercepts marine air and cloud moisture and blocks its inland penetration.…”
mentioning
confidence: 99%
“…This behavior highlights redwood sensitivity to ambient humidity and, consequently, the presence or absence of clouds. In coastally exposed sites, the marine stratus also provides significant quantities of water to coastal California forests (4,7,9,10,22) and grasslands (13), obtained primarily by drip from the canopy to the root zone (6) and to a lesser extent by direct foliar uptake (5,23). Intraannual variations in ÎŽ 18 O and ÎŽ 13 C of redwood tree rings show significant correlations to summer low-cloud frequency over recent years (24), reflecting an integrated effect on redwood physiology.…”
mentioning
confidence: 99%
“…The high organic matter contents (and associated high water holding capacity) and the presence of fog (which reduces evapotranspiration) can both contribute to this characteristic. Decreases in fog water inputs could, however, lead to drier soils (Ewing et al 2009) In contrast to gross nitrification, rates of gross N mineralization in coast redwood forests were relatively insensitive to any variable measured, edaphic or climatic. Other studies have reported a direct relationship between gross N mineralization and substrate availability (Booth et al 2005), and a significant relationship between gross N mineralization and concentrations of soluble organic nitrogen was previously found for two northern redwood sites (Bradbury 2011).…”
Section: Impact Of a Change In Climate On Gross Rates Of N Mineralizamentioning
confidence: 86%
“…Such acid fog deposits on vegetative surfaces and is harmful to plants (Schaberg et al, 2000;Jacobson et al, 1989;Schemenauer, 1986). In addition, fog water deposition significantly contributes to hydrological, nutrient and pollutant inputs to forest ecosystems (Ewing et al, 2009;Fenn et al, 2000;Dawson, 1998), and it may affect the woodland along the somma of Lake Mashu. Nevertheless, the fog water deposition on the woodland in the area, which can cause supply considerable amounts of pollutants and nutrients, has still not been investigated.…”
Section: Introductionmentioning
confidence: 99%